The Quality of the Government Financial Statements: An Empirical Study - Kania Azizah; Khoirul Aswar (Information Management and Business Review, 2022)
This study aims to identify and evaluate the impact of accrual-based government accounting standards, human resources, and internal control on the quality of financial statements in the Ministry of Agriculture Republic of Indonesia Food Security Agency's finances. One central work unit and 34 regional work units dispersed across the provinces make up the Food Security Agency work unit. The Central Food Security Agency work unit will subsequently assemble the financial report into a financial report for Echelon 1 level. This study is quantitative and draws its primary data from the answers to the questionnaires that were given to participants. Only 50 of 70 respondents who participated in the study's samples met the criteria. In this investigation, Smart Partial Least Square 3.0 was also employed, and the Structural Equation Modeling (SEM) approach was used to evaluate the data and test the research's assumptions. The use of accrual-based government accounting standards and internal control has a substantial impact on the caliber of government financial reports, according to the study's findings. Effectiveness of the central government's financial reporting was not significantly impacted by the findings about the human resources' competency, nevertheless. The contribution in this study by the linked work units is to help apply accrual-based government accounting standards in tandem with government regulation No. 71 of 2010 and lower the financial reporting mistake rate. Additionally, it is anticipated that this study will offer data that may be used as input to improve internal control and raise the caliber of government financial statements.